1983
DOI: 10.1038/bjc.1983.76
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood leukaemia in The Netherlands (1973-1980)

Abstract: Summary The childhood leukaemia incidence rate for the Netherlands was estimated at 3.11 per 100.000 children (aged 0-15 year) per year, based on a complete nation-wide childhood leukaemia registry comprising the period [1973][1974][1975][1976][1977][1978][1979][1980]. Acute lymphocytic leukaemia (ALL) accounted for 82.4% of the patients, acute nonlymphocytic leukaemia for 13.6% and chronic myeloid leukaemia for 2.9%. ALL occurred more frequently in boys (sex ratio 1.2). The highest ALL rate was observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 10 publications
2
1
0
1
Order By: Relevance
“…A markedly high incidence of CLL has been given by Kwiat Kowski A [6], Hansen NE et al [10] and Brincker H [22] who reported CLL as being more common than CML in Poland, Denmark and Scandinavia respectively. We found maximum cases of ALL upto 4 years of age as has also been reported by Van Steensel Moll NA et al [16], Clavel J et al [23] and Monge P et al [17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A markedly high incidence of CLL has been given by Kwiat Kowski A [6], Hansen NE et al [10] and Brincker H [22] who reported CLL as being more common than CML in Poland, Denmark and Scandinavia respectively. We found maximum cases of ALL upto 4 years of age as has also been reported by Van Steensel Moll NA et al [16], Clavel J et al [23] and Monge P et al [17].…”
Section: Discussionsupporting
confidence: 89%
“…Among acute leukemias in children, they found 70.3% cases of ALL. Similarly, higher incidence of ALL among acute leukemias has been reported by Van Steensel-Moll HA et al [16], Monge P et al [17], Coeberg JW et al [18] and D Costa G et al [19]. Similarly, we too found a higher incidence of ALL in children.…”
Section: Discussionsupporting
confidence: 89%
“…18 Por otro lado, algunos autores piensan que es la inclusión de algunos factores carcinógenos en el ambiente lo que puede estar propiciando el incremento en la incidencia de LAL. 4,19 Sin embargo, en la ciudad de México este es uno de los primeros trabajos para describir la incidencia de LA y no se tienen datos para señalar cuáles son las causas por las que se puede estar dando un incremento en la incidencia de este padecimiento.…”
Section: Discussionunclassified
“…In a previous epidemiological study the DCLSG register proved to be almost complete. The incidence of childhood leukaemia appeared to be constant in the period 1973-1979(van Steensel-Moll et al, 1983a. The present study covers the period [1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986].…”
mentioning
confidence: 99%